2014
DOI: 10.1021/ie303106z
|View full text |Cite
|
Sign up to set email alerts
|

Connectionist Model to Estimate Performance of Steam-Assisted Gravity Drainage in Fractured and Unfractured Petroleum Reservoirs: Enhanced Oil Recovery Implications

Abstract: Supporting InformationA portion of the actual data employed in the current study is given in Table S1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…Further, since the formation of emulsions result from steam condensate contacting oil near the boundary of the steam chamber (Mohammadzadeh et al, 2012;Zendehboudi et al, 2014;Kar et al, 2014), the role of emulsions on oil flow and solvent mass transfer also needs more study.…”
Section: Proposed Steam-solvent Injection Strategy To Improve Es-sagdmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, since the formation of emulsions result from steam condensate contacting oil near the boundary of the steam chamber (Mohammadzadeh et al, 2012;Zendehboudi et al, 2014;Kar et al, 2014), the role of emulsions on oil flow and solvent mass transfer also needs more study.…”
Section: Proposed Steam-solvent Injection Strategy To Improve Es-sagdmentioning
confidence: 99%
“…It has been demonstrated that heavy oil or bitumen can be produced at rates from 100 to 400 m 3 /day, with the cSOR varying from 2 to 10 m 3 /m 3 (Butler, 1998). Costs are more adverse for a highly fractured reservoir with a typically high cSOR and low oil recovery factor (Zendehboudi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The number of neurons in the input and output layers is decided by the number of input and output variables that are planned for the predictive tool. However, the optimal number of neurons in hidden layer(s) is a strong function of nonlinearity and dimensionality of the problem under study [13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Artificial Neural Network and Particle Swarm Optimizationmentioning
confidence: 99%
“…An activation function processes this sum and gives out the output, . Indeed, the resulting sum is processed by a neuron activation function to obtain the ultimate output of the neuron as follows [13][14][15][16][17][18][19][20][21][22][23][24][25][26]:…”
Section: Artificial Neural Network and Particle Swarm Optimizationmentioning
confidence: 99%
See 1 more Smart Citation